Epithelioid angiomyolipoma with tumor thrombus in IVC and right atrium - Deepika Gupta; Vikarn Vishwajeet; Himanshu Pandey; Mahendra Singh; Binit Sureka; Poonam Elhence (University of São Paulo, 2021)
Epithelioid angiomyolipoma is an uncommon subtype of renal angiomyolipoma associated with potentially malignant behavior and is considered a distinct entity by the World Health Organization classification of renal tumors. We present a case of an epithelioid variant of angiomyolipoma with extension into the renal vein, inferior vena cava reaching up to the right atrium. Pre-operatively, a diagnosis of renal cell carcinoma was considered based on imaging findings. Intra-operatively due to extensive adhesions, surgical resection was not performed and only tissue sampling was performed for histopathology. Microscopic examination revealed short fascicles of spindle cells and perivascular epithelioid cells. A differential diagnosis of renal cell carcinoma with sarcomatoid differentiation was considered. The immunohistochemical profile showed tumor cells that express Melan-A and smooth muscle actin, while they were negative for pan-cytokeratin, PAX8, CK7, CD117 and CD34. Therefore a diagnosis of epithelioid angiomyolipoma was rendered. The presence of intravascular thrombi on radiological investigation and carcinoma-like growth pattern on light microscopy may compound an erroneous diagnosis of renal cell carcinoma. Hence, it is prudent for the urologist to consider differential diagnosis other than renal cell carcinoma when confronted with a renal neoplasm presenting with intravascular thrombi. In these cases, a core biopsy should be planned pre-operatively and diagnosis should be made with aid of appropriate immunohistochemical markers.